(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides information about the integration of collaborative learning strategies into the German language classroom and theoretical foundations, benefits, and practical strategies for this learning method which delves into group activities, partnership, and using technology as effective methodologies, emphasizing the creation of an inclusive and supportive learning environment. Positive impact of collaborative learning on language proficiency and its challenges as well as encouraging further exploration of innovative pedagogical approaches are highlighted and explained during the article.